Canadian Public Policy: The State of the Discipline. Issue 1 (March 2023) - Skogstad, Grace
Abstract: This article examines the state of the English-language peer-reviewed literature published over the 2011–2021 period whose objective is to describe and explain processes of development of Canadian public policies and their consequences. It first presents a profile of the surveyed literature's attention to different policy sectors, elements of public policy, and its chosen methodologies to study them. It then examines the empirical and theoretical contributions of the literature to uncovering the constitutive actors and their interactions in policy processes in policy domains of Canadian jurisdictions; the logics of chosen policy instruments and their distributive effects; and the interactions among Canada's structural, institutional and ideational features and policy actors' motivations and behaviour with processes of policy innovation, continuity and change. A foremost contribution of Canadian policy studies to comparative policy studies is to demonstrate the causal impacts of the interaction of institutional, structural and ideational/cultural factors on processes of policy development.